He ain't heavy, he's my brother - Neo, Crystal V Wen Qian (2009)
“He ain’t heavy, he’s my brother” is a promotional campaign for Boys’ Town that aims to strengthen the client’s brand, raise awareness about its mission and activities, and to correct public misconceptions about Boys’ Town and its boarders. A collaboration between Boys’ Town and faeries, a team of four final-year undergraduates from Nanyang Technological University’s Wee Kim Wee School of Communication and Information, the project involved the use of strategic communication, a series of promotional events and activities, and the introduction of new corporate collaterals and publicity materials. The project seeks to raise awareness for Boys’ Town by engaging tertiary students and the media. More importantly, establish a consistent image for the client in the eyes of the public and to influence positive perception about the organization. The main components of this project are research, publicity, event management, media relations, and evaluation. This report chronicles the various promotional strategies, methods, and tools the team employed to achieve the goals and objectives of the project.